SDG13 - climate action : combating climate change and its impacts - Doni, Federica; Gasperini, Andrea; Torres Soares, João (Concise guides to the United Nations Sustainable Development Goals., 2020)
SDG 13 aims to 'take urgent action to combat climate change and its impact'. This book demonstrates the potential for innovation in implementing SDG13 despite its associated challenges. The book features global success stories and uses empirical and science-based analysis to explore a wide range of practical implementation mechanisms, enabling conditions, and monitoring and reporting tools. Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.